Numerical investigation of buoyancy and thermal radiation effects on a mid-/large-sized low NOx combustion system with flue-gas internal recirculation. (April 2018) - Kwon, Minjun; Nguyen, Ba Hieu; Kim, Sewon; Kim, Yongmo; Park, Jae Hyun
Due to stringent regulations, there has been considerable effort to reduce NOx emissions. In this study, we numerically investigate the details of NOx reduction in a mid-/large-sized combustion system employing a new novel flue-gas internal recirculation burner is thoroughly studied with emphasis on the effects of buoyancy and thermal radiation. The NOx emission in the flue-gas internal recirculation combustion system is observed to be half the value in the non-flue-gas internal recirculation system due to lowered temperature. The present combustion system is large enough for the natural convection to be established and as a result the buoyancy effects become remarkable even though the fuel and air are introduced in the transverse direction. Interestingly, the buoyancy augments the NOx formation in the non-flue-gas internal recirculation system, whereas it reduces the NOx emission in the flue-gas internal recirculation system. Contrary to the thermal radiation, the buoyancy effects in large-sized combustion systems have not been systematically studied yet. Also, the numerical prediction of NOx emission with computational fluid dynamics is accurate only when the buoyancy and thermal radiation are considered together. The present finding about NOx emission, buoyancy, and thermal radiation is expected to be very useful in innovating the ultra-low NOx combustion systems.